Reflection of Eating Awareness and Life Engagement of University Students on the Coronavirus (COVID-19) Pandemic - Önen, Cihan; Sandıkçı, Muhammed Bahadır (Progress in Nutrition, 2021)
Study Objectives: With the restrictions in the pandemic process and the distance education process, changes have occurred in the diet of students. In such periods, which affect human life in a significant way in terms of public health, nutrition must be managed well. The study was conducted to evaluate the eating awareness of university students during the COVID-19 pandemic period and to examine its relationship with their engagement in life. Methods: The population of the cross-sectional study consists of the students of Munzur University. As a precaution regarding the COVID-19 pandemic, the participants were reached on the internet. Results: Eating awareness was statistically higher in men, married people, those with normal weight, and older students. While the life engagement among university students was high, the mean scores of eating awareness and its sub-components were moderate. Life engagement was significantly higher in sports science students than students in other academic units. There was a weak but significant relationship between eating awareness and engagement in life. Conclusion: Eating awareness of university students during the pandemic is at a moderate level. Students with high eating awareness are attached to life more. The highest life engagement among academic units is among sports science students. There is a need for public health initiatives to increase the awareness of eating among the students, against COVID-19 and possible future pandemics.